A Research Study on Tobacco Associated Oral Potentially Malignant Disorders (OPMDs) Prevalent in Oral Mucosa of Lumbini Province/District Rupandehi Population of Nepal - Siddharth Gupta; Pratik Man Shrestha (Athens Journal of Health and Medical Sciences)
Background: Tobacco associated Oral mucosal lesions (OML) oral potentially malignant disorders (OPMDs) that comprise of oral sub-mucous fibrosis, oral leukoplakia, tobacco pouch keratosis, chewer’s mucositis, pan encrustation are the most prevalent diseases in Rupandehi District, Lumbini province (Province Five) of Nepal. These OPMDs are usually caused by the consumption of both smokeless and smoked forms of tobacco. Smoking, chewing of the tobacco products including alcohol consumption are the common prevalent habits in Nepal and have been positively associated with such lesions. Aim of the Research Study: With this background, a research study has been conducted to assess the prevalence of OPMDs and their association among the patients visiting the outpatient department in Rupandehi district of Nepal. Research Methods and Material: This descriptive, cross-sectional prevalence study included five hundred participants who visited the Outpatient Department and fulfilled the inclusion criteria. The study data was carried out from August 2003 till April 2024. Institutional Review Committee (IRC) provided the ethical clearance to the study, which was duly obtained along with patient consent that were part of the study. Standardised proforma was used for recording demographic details, and WHO Assessment form for oral mucosal lesions were used to record the tobacco use status and findings of the clinical and laboratory investigations. Statistical analysis was performed using IBM SPSS version 23, and the results were calculated along with the level of significance. Research Study Results: The final sample was comprised of 500 cases of which 392 were males and 108 were females. The mean age of the study population was 58.19 ± 12.33 years (p<0.001). Leukoplakia in its varied forms (OPMD) accounted for almost 82% of the sample cases. The lesions from patients aged from 41 to 80 years presented moderate and severe dysplasia more often than lesions from patients in other age groups. The prevalence of tobacco use among study participants was 41.25% and that of the OML (oral mucosal lesions) positively attributed with use of tobacco was 39.28%. Tobacco chewing (areca nut) were significant predictors of oral sub mucous fibrosis in this population. Conclusion: The prevalence study emphasizes the deleterious effects of tobacco use on oral mucosa and also serves as a path for future tobacco cessation programs that would be helpful to prevent OPMDs in the Nepalese population especially in Province V (Rupandehi District) of Nepal.